Green Design Initiatives in the UAE Construction Sector - Amritha Achuthan, Amritha (2009)
The UAE has been progressing steadily on the path of growth and development over the last three decades, propelled by an oilrich economy. In an economy largely based on hydrocarbon production, managing carbon emissions is a major challenge. Carbon footprint statistics suggest that UAE is an environmental disaster. But in the past 2 years eco‐friendly initiatives have gained momentum in various sectors. With the recent Dubai government’s directive proposing a regulation that requires all buildings in Dubai to adhere to strict green standards, efforts in the construction industry towards green initiatives, in both public and private sector have gained pace. Though along with it are a series of speculation regarding its desired impact, and its immediate effect on the already volatile construction industry. Construction professionals need to educate themselves of green design, be informed of the whole lifecycle process and environmental impact of buildings so that they can encourage key stakeholders to make more sustainable choices. The thesis tries to better understand this process of sustainability in design, and its implications in Dubai. A compilation of the international green design practices along with its supporting regulations in Dubai are summarized to form a handy tool to future designers. The study methodology forms LEED rating system as its basis and verifies design aspects suitable for UAE through interactive discussions with designers, government officials, LEED facilitators along with active involvement in the design process. Parallel case studies of green buildings operational in the region are examined to verify the applicability of the data learnt. The study summarizes on the need for an Integrated Design Process as a key factor for successful green buildings as a primary conclusion from the research. A list of key sustainability elements to be implemented in green design and regulatory application guidelines for Dubai are compiled. By doing so, the writer hopes to contribute towards sustainable UAE and address the worldwide environmental challenge.